Everyone Will Be Jealous For That Mutika - Gerrard, Grayson (The Australian journal of anthropology, 1989)
In this paper I describe a phenomenon I refer to by its Aboriginal English name — ‘humbugging’ — in a western Arnhem Land Aboriginal settlement. By discussing the focal object in this phenomenon — the ‘mutika’ (car)1 — I argue that a most interesting process of de-commoditization is occurring in this settlement. I use examples of humbugging to illustrate how the car in this community has tremendous symbolic as well as practical significance. I use. in particular, the work of Douglas and Isherwood (1979) and Appadurai et al. (1986), and argue that their ‘social life of things’ theoretical framework is appropriate for interpreting the importance of the ‘mutika’. I also suggest, however, that this framework needs to be re-thought in order to incorporate the challenge which de-commoditization presents to it.